2022
DOI: 10.1177/07334648221130323
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ageism in Climate Change Worries and Willingness to Act

Abstract: This study examined the association of negative ageist prescriptive expectations regarding older people with worries about climate change and willingness to act. An online survey was completed by 250 Australians over the age 18. Higher levels of ageism (e.g., negative prescriptive views towards older people) were associated with fears about the impact of climate change on one’s life, worries about the impact of climate change on older members of the family, and willingness to pay higher taxes to fight climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…In their effort to shine light upon such injustices and climate inaction, many activists have taken refuge in sentiments that may negatively impact intergenerational relations. A recent study has found that negative views about older adults may motivate people to deeply consider the impacts of climate change and increase their willingness to pay higher taxes in support of climate action [35]. Negative perceptions, however, may also lead to increased ageism towards older adults who might feel unfairly victimized and withdraw support from climate action, thereby increasing the risk to the health and wellbeing of all.…”
Section: Discussionmentioning
confidence: 99%
“…In their effort to shine light upon such injustices and climate inaction, many activists have taken refuge in sentiments that may negatively impact intergenerational relations. A recent study has found that negative views about older adults may motivate people to deeply consider the impacts of climate change and increase their willingness to pay higher taxes in support of climate action [35]. Negative perceptions, however, may also lead to increased ageism towards older adults who might feel unfairly victimized and withdraw support from climate action, thereby increasing the risk to the health and wellbeing of all.…”
Section: Discussionmentioning
confidence: 99%
“…Next, respondents were asked to indicate their agreement or disagreement with the following attitudinal, emotional and behavioral climate change items, respectively: “climate change is a real phenomenon that impacts earth”; “I worry about the impact of climate change on my life;” “I worry about the impact of climate change on younger members of the family:” “I worry about the impact of climate change on older members of the family:” “I am willing to pay higher taxes to fight climate change.” These items were ranked on a seven-point scale, ranging from fully disagree to fully agree. Climate change items have shown evidence of face validity based on experts’ assessment and were used in past research [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Climate change anxiety among the young (Wu et al, 2020 ), coupled with a strong emphasis on personal responsibility for climate change, may actually increase ageism. Possibly blaming others (e.g., holding prescriptive ageist views toward older people) serves as an incentive to take climate change action (Ayalon & Roy 2023 ). In 2019, the phrase “OK, Boomer” went viral on social media platforms, and became a slogan for “Millennials” who felt “Baby Boomers” were out‐of‐touch with modern problems such as global climate change (Meisner, 2021 ).…”
Section: Intergenerational Conflict and Ageismmentioning
confidence: 99%